Sharia-Compliant Digital Marketing: Trends and Challenges in Indonesia's Financial Sector (2024-2025) - Dio Samudra; Tamamudin Tamamudin (International Publisher (YAPENBI), 2025)
The rapid digitalization of Indonesia's financial sector has created unprecedented opportunities and challenges for Sharia-compliant institutions seeking to expand their market reach while adhering to Islamic principles. This literature review examines the current trends and challenges in digital marketing practices among Indonesian Islamic financial institutions from 2024 to 2025. Through a systematic analysis of 45 peer-reviewed articles, regulatory documents, and industry reports, this study identifies key developments in Sharia-compliant digital marketing strategies, including the adoption of artificial intelligence, social media engagement, and mobile-first approaches. The findings reveal that while Indonesian Islamic financial institutions have successfully leveraged digital platforms to enhance customer acquisition and retention, significant challenges persist in ensuring full Sharia compliance in digital advertising, managing cybersecurity risks, and addressing the digital divide among target demographics. The research identifies four primary trends: increased use of Islamic fintech partnerships, personalized halal investment recommendations through AI, community-driven social media campaigns, and blockchain-based transparent financial products. Key challenges include regulatory ambiguity regarding digital Sharia compliance, competition from conventional digital banks, limited digital literacy among traditional Islamic banking customers, and the need for specialized talent in both Islamic finance and digital marketing. This study contributes to the growing body of knowledge on Islamic digital finance by providing a comprehensive overview of current practices and offering strategic recommendations.